2010
DOI: 10.1158/1541-7786.mcr-09-0417
|View full text |Cite
|
Sign up to set email alerts
|

The Intracellular Delivery of a Recombinant Peptide Derived from the Acidic Domain of PIAS3 Inhibits STAT3 Transactivation and Induces Tumor Cell Death

Abstract: Signaling components, which confer an "addiction" phenotype on cancer cells, represent promising drug targets. The transcription factor signal transducers and activators of transcription 3 (STAT3) is constitutively activated in many different types of tumor cells and its activity is indispensible in a large fraction. We found that the expression of the endogenous inhibitor of STAT3, protein inhibitor of activated STAT3 (PIAS3), positively correlates with STAT3 activation in normal cells. This suggests that PIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 43 publications
1
52
0
Order By: Relevance
“…STAT3 inhibition can also be affected by peptides (5,17,38). Our study indicates that the uptake of a STAT3-inhibiting peptide into mesothelioma cells is effective and induces cell growth inhibition and apoptosis.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…STAT3 inhibition can also be affected by peptides (5,17,38). Our study indicates that the uptake of a STAT3-inhibiting peptide into mesothelioma cells is effective and induces cell growth inhibition and apoptosis.…”
Section: Discussionmentioning
confidence: 63%
“…Protein purification of the peptide rPP-C8 and cell treatment was performed as described previously (17). Briefly, 2,000 cells were seeded in 96-well plates, and the next day, medium was removed, 0.5 or 2.0 mmol/L of the peptide (or PBS as solvent control) was diluted in 100 mL medium and added to the cells.…”
Section: Purification and Cell Treatment Of Peptide Rpp-c8mentioning
confidence: 99%
See 1 more Smart Citation
“…L97 and R99 are part of a potential binding surface and mutations of L97 and R99 of the PINIT domain abrogate binding to STAT3 39. In addition, the acidic region of the carboxyl terminal of PIAS3 can specifically bind to the rPP‐C8 region of STAT3, thereby inhibiting the proliferation and promoting the apoptosis of tumour cells 40. Therefore, miR‐181b might inhibit the expression of PIAS3 and directly bind to the PINIT domain of PIAS3 (PIAS3 82‐132 , PIAS3 85‐272 , and/or L97&R99).…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous administration of rS3-PA into mice showed that the systemic application of rS3-PA inhibits Stat3 activation in vivo and slightly retarded the growth kinetics of transplanted glioma cells. 13 An alternative strategy was used to derive a survivin inhibiting molecule. A cDNA library was screened in a yeast two-hybrid setting for survivin-interacting proteins.…”
Section: Inhibition Of Stat3 and Survivin Through Peptide Ligandsmentioning
confidence: 99%